Social Image in the Online Environment Sustainable Motive for Book Sales During the Pandemic - Corina Pelau; Valentina Ghinea; Bogdan Hrib (Amfiteatru Economic, 2023)
Social distancing and the work-from-home setting have determined the development and success of online communication platforms. Most of the communication during the social distancing period took place online, allowing people access to the homes and offices of those with whom they communicated. Since social image is an important aspect of human existence, during pandemics there has been a tendency to translate the attention for social image from real life into the communication carried out through on-line platforms. The use of books as a background for communication through on-line platforms fosters an intellectual image of the respective user, and thus becomes a considerable buying reason during the pandemic. The objective of our research is to determine whether a good-looking, interesting, and attractive book shelf used as a background on online communication platforms is a good reason to buy books during the pandemic. In a mediation model, we empirically demonstrate that the perception that the presence of books confers an intellectual look, mediated by the fact that a background with books induces an intellectual image, becomes a valid buying motive for books. This result has important implications for the future book sales strategy and highlights the major role played by the aspect of book covers in sustainable future sales. Attention is also driven to a slightly superficial development of the digital society we live in, where appearance is often more important than essence. For a sustainable development of our society, it is important to intervene in the educational system and put more emphasis on content and not just on appearances.
Keywords: M30; M31; 330; Consumer; book; online communication platform; pandemic; buying motives; snob effect.